Intimate partner violence and post-migration stressors reported by refugee women accessing settlement services - Jo Spangaro; Nigel Spence; Nicola Man; Jeannette Walsh; Jacqui Cameron; Kelsey Hegarty; Jane Koziol-McLain; Tadgh McMahon; Anthony Zwi; Chye Toole-Anstey; Astrid Perry-Indermau (BMC Women's Health)
Abstract Intimate partner violence (IPV) is highly prevalent globally, with increased risk for women in situations of conflict, post conflict and resettlement. The Safety and Health after Arrival (SAHAR) study tested IPV screening with women accessing settlement services in New South Wales, Australia, using the validated ACTS tool, along with brief response involving risk assessment, safety planning and referral. A three month follow-up telephone survey was administered to women who had attended four participating sites which delivered the intervention. The survey explored the nature of any IPV experienced, factors associated with disclosure, and responses provided to those who identified IPV. Data is reported on 316 women of whom 48 (15%) identified current IPV. For 45 women who responded to Composite Abuse Scale items, the most common forms of abuse were forced isolation from family/friends (56% 25/45), blame for abusive behaviour (53% 24/45), “put downs” (44% 20/45) and physical violence 38% (17/45). Psychological distress and post-migration stressors were significantly higher for women who disclosed IPV compared to those who did not. Length of residency in Australia and whether the screening occurred during the first or subsequent service visits, were not associated with the likelihood of disclosing IPV. The majority of women who disclosed reported the caseworker’s response to be helpful and involved risk assessment, safety planning and referral. Screening and response to disclosure in settlement services provide opportunities to address abuse experienced by this group of women who are less likely to report experiences of abuse or use mainstream services.